العمالة الوافدة وتكاليفها الاقتصادية في العراق: Expatriate Workers and Its Economic Costs In Iraq - سونيا آرزروني وارتان (Journal of North African Economies, 2025)
The instructions for the entry of expatriate workers to Iraq are in accordance with labor law no. 1 of 1987 and no. 37 of 2015. Therefore, the study aims to know its classification according to its type skilled (skilled / semi-skilled / unskilled) and the pattern of demand for it (its weight in the public sector compared to the private sector) and (job specialization),hence, reliance on it is due to several factors, including (low wages/obedience and efficiency at work/the cultural factor/the emergence of many fake institution , etc).However, at the same time, it has economic costs, namely (positive: insignificant), (negative: dominant), and the latter on the state, companies, individuals and society .The study reached several results, the most important of which are (the enactment of laws that prevent their entry after achieving the full use of human energies / the application of tax on their income, , etc.).